Ecclesiastes 1-5 a critical and exegetical commentary - Weeks, Stuart 1964- ([London, England] T & T Clark Ltd, 2020)
"This new volume in the ICC on Ecclesiastes 1-5 brings together all the relevant aids to exegesis - linguistic, textual, archaeological, historical, literary and theological - to enable the scholar to have a complete knowledge and understanding of this Old Testament book. Stuart Weeks incorporates new evidence available in the field, surveys the wealth of secondary literature and provides an extensive introduction to Ecclesiastes as a whole."--
Preface -- Introduction -- Commentary -- Bibliography.
Includes bibliographical references
Also published in print.
Reproduktion
Mode of access: World Wide Web.
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Bible -- Commentaries; Bible -- Criticism, interpretation, etc; Biblical studies & exegesis; Electronic books